PENGEMBANGAN MEDIA PEMBELAJARAN MENULIS SURAT BAHASA JERMAN - Ahmad Sahat Perdamean; Tanti Kurnia Sari (BAHAS, 2019)
This study aims to develop a media of letter-writing (Brief). The reference of this research is the design of material development by Jolly and Bolito (in Tomlinson, 1998:96) consisting of: i. Identification of material needs, ii. Exploration needs, iii. Contextual realization, iv. The realization of pedagogy, v. The preparation of the material includes the use of the product by the learners, vi. Evaluation of material in accordance with material development objectives. The research instruments used are: a. Instrument of student response to instructional media, b. Instrument observation of student activity in learning, c. documentation, d. Test and assessment criteria in the ZiDS-exam to find out student learning outcomes. Development of learning media to write letters (Brief) in accordance with the procedures that have been determined and have good quality because it is valid, practical and effective. The application of learning media to write letters proved to improve the learning achievement of student writing skill, from 76,92% to 100% from 26 people able to write reply letter. Thus the learning media to write letters feasible to be used in lectures Schreibfertigkeit subject and to be a supporting medium for students.Kata kunci: pengembangan bahan, media pembelajaran, keterampilan menulis